Aflatoxin-Exposure of Vibrio gazogenes as a Novel System for the Generation of Aflatoxin Synthesis Inhibitors - Gummadidala, Phani M.; Chen, Yung Pin; Beauchesne, Kevin R.; Miller, Kristen P.; Mitra, Chandrani; Banaszek, Nora; Velez-Martinez, Michelle; Moeller, Peter D. R.; Ferry, John L.; Decho, Alan W.; Chanda, Anindya (Frontiers in Microbiology, 2016)
Aflatoxin is a mycotoxin and a secondary metabolite, and the most potent known liver carcinogen that contaminates several important crops, and represents a significant threat to public health and the economy. Available approaches reported thus far have been insufficient to eliminate this threat, and therefore provide the rational to explore novel methods for preventing aflatoxin accumulation in the environment. Many terrestrial plants and microbes that share ecological niches and encounter the aflatoxin producers have the ability to synthesize compounds that inhibit aflatoxin synthesis. However, reports of natural aflatoxin inhibitors from marine ecosystem components that do not share ecological niches with the aflatoxin producers are rare. Here, we show that a non-pathogenic marine bacterium, Vibrio gazogenes, when exposed to low non-toxic doses of aflatoxin B1, demonstrates a shift in its metabolic output and synthesizes a metabolite fraction that inhibits aflatoxin synthesis without affecting hyphal growth in the model aflatoxin producer, Aspergillus parasiticus. The molecular mass of the predominant metabolite in this fraction was also different from the known prodigiosins, which are the known antifungal secondary metabolites synthesized by this Vibrio. Gene expression analyses using RT-PCR demonstrate that this metabolite fraction inhibits aflatoxin synthesis by down-regulating the expression of early-, middle-, and late- growth stage aflatoxin genes, the aflatoxin pathway regulator, aflR and one global regulator of secondary metabolism, laeA. Our study establishes a novel system for generation of aflatoxin synthesis inhibitors, and emphasizes the potential of the under-explored Vibrio’s silent genome for generating new modulators of fungal secondary metabolism.